2007
DOI: 10.1111/j.1365-2125.2007.02864.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitroglycerin protects the endothelium from ischaemia and reperfusion: human mechanistic insight

Abstract: What is already known about this subject • The production of oxygen free radicals upon administration of nitroglycerin (GTN) and other organic nitrates has been advocated as one of the causes of nitrate-induce tolerance and endothelial dysfunction.• It has been shown that nitrates also cause a protective phenomenon that is similar to ischaemic preconditioning, but the mechanisms of this effect have never been investigated in humans. Aims Nitroglycerin (GTN) modulates tissue damage induced by ischaemia and repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 27 publications
7
64
2
3
Order By: Relevance
“…Radial artery diameter and radial artery blood flow returned to baseline values 15 min after local IR ( (10,12,14,15). Reproducing previous findings from our laboratory, rosuvastatin administration prevented the impairment in FMD associated with IR ( Fig.…”
Section: Acute Administration Protocolsupporting
confidence: 70%
See 1 more Smart Citation
“…Radial artery diameter and radial artery blood flow returned to baseline values 15 min after local IR ( (10,12,14,15). Reproducing previous findings from our laboratory, rosuvastatin administration prevented the impairment in FMD associated with IR ( Fig.…”
Section: Acute Administration Protocolsupporting
confidence: 70%
“…The methods for assessment of FMD and blood flow in our laboratory (12,14,15,25), as well as the repeatability of FMD measurements, have been previously described in detail. Briefly, end-diastolic, ECG-gated, longitudinal, B-mode images of the artery 10 -15 cm below the antecubital fossa were digitally acquired and stored for offline analysis.…”
Section: Measurement Of Arterial Diameter and Fmdmentioning
confidence: 99%
“…Conversely, we recently demonstrated (14) that GTN-triggered ROS production is responsible for GTN-induced preconditioning, in a paradoxically protective effect of ROS. We also demonstrated that mPTP opening is crucial for this latter property of GTN (4). Because mPTP and K-ATP channel opening can theoretically be up-and downstream of GTN-induced ROS (10), the present study tested whether inhibition of these channels or of GTN biotransformation prevents GTN-induced ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Of importance, we recently documented that exposure to GTN causes a rapid increase in mitochondrial reactive oxygen species (ROS) production (2), and it has been shown that this may depend on the uncoupling of the mitochondrial respiratory chain (3). Furthermore, we recently demonstrated that this GTN-triggered ROS production is responsible for GTN-induced ischemic preconditioning (a short-term beneficial effect of GTN-induced ROS) (4) and GTN tolerance occurring in concert with the development of endothelial dysfunction (a long-term toxic effect of GTN-derived ROS) (5). It has also been demonstrated that opening of the mitochondrial permeability transition pore (mPTP) is critical in GTN-induced preconditioning (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation